ACE, XL, MID OCEAN AND MRM AND THE BERMUDA MARKET - Anderson, Dan R. (Assurances, 1998)
This article discusses the development of four key organizations in the Bermuda market, ACE, XL, Mid Ocean and Mutual Risk Management Ltd. Several common factors among these four corporations, which have contributed to their considerable success, are examined. Several of those factors are becoming defining characteristics of modern risk financing groups. These four organizations have been instrumental in transforming Bermuda into one of the world's leading risk financing markets. The article concludes with a discussion of future challenges for these four groups and Bermuda market.